2013
DOI: 10.1111/ppl.12037
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of Citrus macrophylla BOR1 as a boron transporter

Abstract: Plants have evolved to develop an efficient system of boron uptake and transport using a range of efflux carriers named BOR proteins. In this work we isolated and characterized a boron transporter of citrus (Citrus macrophylla), which was named CmBOR1 for its high homology to AtBOR1. CmBOR1 has 4403 bp and 12 exons. Its coding region has 2145 bp and encodes for a protein of 714 amino acids. CmBOR1 possesses the molecular features of BORs such as an anion exchanger domain and the presence of 10 transmembrane do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 58 publications
0
30
0
3
Order By: Relevance
“…Recently, BOR1 has been reported to have a similar function in other species, including OsBOR1 in rice (Nakagawa et al 2007), TaBOR1 in wheat (Leaungthitikanchana et al 2013), VvBOR1 in grape (Vitis vinifera L.) (Perez-Castro et al 2012) and CmBOR1 in Citrus macrophylla Wester. (Cañon et al 2013). In B. napus, six genes, BnBOR1;1a, BnBOR1;1c, BnBOR1;2a, BnBOR1;2c, BnBOR1;3a and BnBOR1;3c, have now been isolated and characterized (Sun et al 2012).…”
Section: Cloning and Characteristics Of B Transporter Genesmentioning
confidence: 99%
“…Recently, BOR1 has been reported to have a similar function in other species, including OsBOR1 in rice (Nakagawa et al 2007), TaBOR1 in wheat (Leaungthitikanchana et al 2013), VvBOR1 in grape (Vitis vinifera L.) (Perez-Castro et al 2012) and CmBOR1 in Citrus macrophylla Wester. (Cañon et al 2013). In B. napus, six genes, BnBOR1;1a, BnBOR1;1c, BnBOR1;2a, BnBOR1;2c, BnBOR1;3a and BnBOR1;3c, have now been isolated and characterized (Sun et al 2012).…”
Section: Cloning and Characteristics Of B Transporter Genesmentioning
confidence: 99%
“…Under low B conditions, the transport pathways of B from the Arabidopsis root surface to the shoot includes at least three events: (1) NIP5;1, a major boric acid channel, efficiently facilitates B uptake from soil into the root (Takano et al, 2006;Wang et al, 2017); (2) BOR1, a B efflux transporter, is responsible for xylem loading of B (Noguchi et al, 1997;Takano et al, 2002); and (3) NIP6;1 and NIP7;1, homologues of NIP5;1, are required for proper distribution of boric acid in developing shoot tissues and anthers (Routray et al, 2018;Tanaka et al, 2008). Recently, more B transport-related genes, such as tassel-less1 (co-orthologue of AtNIP5;1) (Matthes et al, 2018) and rotten ear (co-orthologue of AtBOR1) (Chatterjee et al, 2014) in maize, OsNIP3;1 (a homologue of AtNIP5;1) (Hanaoka et al, 2014;Shao et al, 2018) and OsBOR1 (a homologue of AtBOR1) (Nakagawa et al, 2007) in rice, VvBOR1 in grapevine (P erez-Castro et al, 2012), CmBOR1 in citrus (Cañon et al, 2013) and TaBOR1s in wheat (Leaungthitikanchana et al, 2013), have been reported. These studies demonstrated that both boric acid channel NIPs (nodulin 26-like intrinsic proteins) and B transporter BORs are critical for plants to cope with B stress.…”
Section: Introductionmentioning
confidence: 99%
“…De igual manera, se analizó la expresión del gen BOR1, que modula el transporte de B en plantas a nivel de la entrada al xilema, regulando la translocación de las raíces a la parte aérea (Takano et al, 2002). En cítricos, se ha realizado recientemente la caracterización funcional del gen CmBOR1 en C. macrophylla (Cañon et al, 2013). La cantidad de transcrito de éste gen en las raíces no varía al aplicarse una concentración alta de B en el medio y la actividad del transportador permite acumular eficientemente el B en las hojas, aun cuando la cantidad en el medio externo sea excesiva (Cañon et al, 2013;Martínez-Cuenca et al, 2015).…”
Section: Discussionunclassified
“…Los cebadores utilizados son los descritos en publicaciones previas Cañon et al, 2013) y se muestran en la Tabla 4.1. Se realizaron tres réplicas técnicas simultáneas de cada reacción y tres réplicas biológicas sucesivas.…”
Section: Extracción De Arn Y Análisis Qrt-pcrunclassified
See 1 more Smart Citation